POTRET KEMASAN MINUMAN JANJI JIWA SEBAGAI MEDIA PENCITRAAN DI SOSIAL MEDIA INSTAGRAM - Renzy Ayu Rohmatillah (Jurnal Ilmu Budaya, 2023)
This research mainly discussed the phenomenon of photo-sharing on Instagram with different aims. One of them was to show a person's identity or a particular group. This study specifically examined a beverage brand growing rapidly on Instagram named "Janji Jiwa", which is being popular among society in Indonesia. As an evidence, the brand once was awarded the fastest-growing coffee shop of the year by MURI (Indonesian Record Museum) in 2019. This research applied a theoretical approach that using the spectacle concept proposed by Guy Debord (2002). In addition, this current study aimed to provide an interpretation linked to the phenomenon of conveying self-identity within social media. Distributing the captured the "Janji Jiwa" beverage could be seen as the act of showing one's social class. Spectator saw the performer not as himself, but based on the commodities he was taking or using In this case, the spectator was consumer of the brand itself. Showing a capture of beverage, precisely "Janji Jiwa", was one's manner for presenting themselves as he built a desired reality. It celebrated a pseudo-identity represented on by social media. Showing off a commodity was meant as an effort to point out a desired image because it was able to give the impression of a prestigious social status.